Effect of thoracic epidural anesthesia on oxygen delivery and utilization in cardiac surgical patients scheduled to undergo off-pump coronary artery bypass surgery: A prospective study - Suryaprakash Sharadaprasad; Chakravarthy Murali; Gautam Mamatha; Gandhi Anurag; Jawali Vivek; Patil Thimmannagowda; Jayaprakash Krishnamoorthy; Pandey Saurabh; Muniraju Geetha (Annals of Cardiac Anaesthesia, 2011)
To evaluate the effect of thoracic epidural anesthesia (TEA) on tissue oxygen delivery and utilization in patients undergoing cardiac surgery. This prospective observational study was conducted in a tertiary referral heart hospital. A total of 25 patients undergoing elective off-pump coronary artery bypass surgery were enrolled in this study. All patients received thoracic epidural catheter in the most prominent inter-vertebral space between C7 and T3 on the day before operation. On the day of surgery, an arterial catheter and Swan Ganz catheter (capable of measuring cardiac index) was inserted. After administering full dose of local anesthetic in the epidural space, serial hemodynamic and oxygen transport parameters were measured for 30 minute prior to administration of general anesthesia, with which the study was culminated. A significant decrease in oxygen delivery index with insignificant changes in oxygen extraction and consumption indices was observed. We conclude that TEA does not affect tissue oxygenation despite a decrease in arterial pressures and cardiac output.